O papel da biblioteca pública municipal de Arraias - TO na perspectiva de usuários e de alguns profissionais que trabalham no local - OLIVEIRA Leidyslane Monteiro de (Universidade Federal do Tocantins, 2021)
The main purpose of this study was do identify the uses and functions of the Edinéia Cordeiro dos Santos Municipal Public Library, located in the municipality of Arraias-TO, a space of paramount importance for the acquisition and production of knowledge and which has important sercices for the community. Aa specific objectives, the following stand out: a) to identify and analyze the works carried out by the library in promoting reading; b) identify the profile of users; c) apprehend the importance of the role of the library for these users; d) highlight the reasons why users look for this space. The work whas based on the definitions and conceptions of some authors, such as Milanesi (1998), Cordeiro (1987), Souza (2009), among others, in addition to consulting official documents. The methodology adopted was based on a qualitative approach that relied on different research instruments, such as observing the library environment, with notes in a diary, and conducting a semi- structured interview, all in the year 2019: in 2020, questionnaires were applied digitally . From the data collected and the analyzes carried out, it was possible to identify that the Municipal Public Library Edinéia Cordeiro dos Santos has some shortcomings and it is necessary that the public authorities invest more to improve the quality of care in the space, as Public Library has as primary function is to provide intellectual development, stimulate knowledge and preserve local culture, being na environment of fundamental importance for the development of a city. In this sense, the aforementioned library needs to expand and update the collection, hiring specialized professional to work in the environment, the need to renovate the space, among other aspects.